2019
DOI: 10.15298/euroasentj.18.1.03
|View full text |Cite
|
Sign up to set email alerts
|

True bugs (Heteroptera) on Ambrosia artemisifolia L. in southern areas of Primorsky Krai, Russia

Abstract: Резюме. Приведены сведения о видах полужесткокрылых (Heteroptera), собранных на амброзии, их трофических связях, а также возможных повреждениях наносимых клопами растению. На амброзии обнаружено 13 видов клопов, принадлежащих к 8 семействам. В их числе 10 видов многоядных фитофагов (Adelphocoris triannulatus, Homoeocerus dilatatus, Molipteryx fuliginosa, Megalotomus junceus, Rhopalus maculatus, Eurygaster testudinaria, Carpocoris purpureipennis, Dolycoris baccarum, Carbula putoni, Menida violacea), и 3 вида (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A study of dietary preferences of two leaffooted bug species (Aistova et al 2019;Markova et al 2019;2020;2021a) identified the following food plants as common for their diet (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A study of dietary preferences of two leaffooted bug species (Aistova et al 2019;Markova et al 2019;2020;2021a) identified the following food plants as common for their diet (Table 1).…”
Section: Resultsmentioning
confidence: 99%